PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA KEMIRI KECAMATAN PANTI KABUPATEN JEMBER - Nisa, Firdasari Khoirun; Ani, Hety Mustika; Hartanto, Wiwin (Universitas Muhammadiyah Tangerang, 2023)
This study aims to describe community participation in the development of Kemiri Tourism Village, Panti District, Jember Regency. This research is a type of descriptive qualitative research. Data collection methods used in this study are in depth interviews, observation and documentation. While the data analysis used in this research are data collection, data reduction, data display and conclusion drawing. The results of this study indicate that not all of the participation went well and optimally. Community participation in decision making can be said to be good, community participation in the implementation as reflected in the contribution of energy and information dissemination can be said to be good, while in the form of donations of funds and materials it can be said to be very lacking. Community participation in taking benefits can be said to be quite good and community participation in evaluation can be said to be quite good. Efforts to develop Kemiri Tourism Village are carried out by developing tourist attractions and promoting through social media.